Passivated ZnSe nanocrystals prepared by hydrothermal methods and their optical properties - Peng, Lingling; Wang, Yuhua; Dong, Qizheng; Wang, Zhaofeng (Nano-Micro Letters, 2010)
Homogeneous ZnSe nanocrystals were prepared via surfactant-assisted hydrothermal method. Surfactants agent CTAB was used to control the particle morphology and the growth rate. The structure, morphology and optical properties of ZnSe nanocrystals have been investigated by XRD, TEM and luminescence spectroscopy. The results indicated that the size of ZnSe nanocrystals ranged from 3.0 nm to 5.0 nm with cubic zinc blende structure. ZnSe nanocrystals coated by CTAB were revealed high dispersibility and distribution under TEM. Compared to the bulk ZnSe, the absorption edges and photoluminescence peaks of ZnSe nanocrystals were blue shifted to higher energies due to the quantum confinement effect. The emission intensity was strengthened after coated CTAB compared to bare sample. This was mainly due to the surface passivation. Meanwhile, we simply explored the formation mechanism of ZnSe nanocrystal in hydrothermal system.